Fundamentals of buffer overflow attacks and detection techniques - Bogdan Barchuk (World Journal of Advanced Research and Reviews, 2025)
Buffer overflows remain a major security risk to software. The article presents the fundamentals of finding buffer overflow weaknesses and methods of analyzing them. Manual and automated fuzzing approaches allow the discovery of possible instances of the stack overflow attack. Immunity Debugger aids in discovering crashes, scrutinizing register clusters, and precisely determining the point at which buffer overflows occur within the memory of a program. Other approaches for identifying and eliminating such “badbytes” are also addressed. The study addresses approaches for bypassing the security measures implemented in contemporary OSs such as ASLR and DEP. This paper provides scripts and case studies allowing security experts and researchers to effectively locate, characterize, and remove far more vulnerabilities related to buffer overflows in many software systems.